A study of common defect at British Colonial Building / Mohd Fauzan Husaini - Husaini, Mohd Fauzan (Faculty of Architecture, Planning and Surveying, 2010)
The dissertation is to study about common defect at British colonial building and scope of study is in Klang Valley. British colonial building have a unique architecture! styles and design and also has a heritage value for the country. This building from era colonial can be says give an impact for surrounding another thing, to shown the British authorithy as a big colonial authorithy and economy. The purpose a lot of colonial building is impliment a design style is to shown the architecture style and its not only come from British, but this design styles is influences from other country such as India and China. In this study, the objectives of this dissertation will be set first. The objective of this dissertation is to focusing on identify defect are common occur at British colonial building. From this objective, details informations about detail of British colonial building in Malaysia, types of defect, common causes of defect is occur and effect of defect if no remedial action are being explained based on the literature review in chapter two. Then, research methodology in chapter three is discuss about a continuous steps to complete this dissertation. Besides, on chapter four, it is focus on case studies. Four case studies has selected which all of building are located at Klang Valley. The case study building is at Keretapi Tanah Melayu Headquarters, Masjid Jamek Kuala Lumpur, Coliseum Theatre and Federal Territory Syarie Court. At the next chapter is discuss about analysis of data from questionnaires and interviews survey. Finally, the conclusion and recommendations of this study will be showed for future study.